Biological processes in solar lentigo: insights brought by experimental models. Issue 3 (March 2016) - Goorochurn, Ranesha; Viennet, Cécline; Granger, Corinne; Fanian, Ferial; Varin‐Blank, Nadine; Roy, Christine Le; Humbert, Philippe
Abstract: Common in ageing patient, the solar lentigo is a macular hyperpigmented skin lesion that results from chronic exposure to ultraviolet irradiations. Despite sharing numerous features with other pigmented spots, the diagnostic of this benign lesion is well characterized at the tissue level. Recent studies shed lights on several factors and their pathogenic mechanisms involved in the development of the solar lentigo. This review summarizes how diverse experimental approaches allowed the identification of several biomarkers, which contribute to a better understanding on the initiation and the maintenance of this pigmentary disorder.